Dompunese and Bimanese Common Idiom “Kalembo Ade”: Morphological, Syntactical, and Semantic Analysis - Ismail, Ismail; Suryaningsih, Lili; Taufik, Taufik; Marlina, Leni (INTERACTION: Jurnal Pendidikan Bahasa, 2022)
This study aims to semantically, morphologically, and syntactically analyze Dompunese and Bimanese common idiom “Kalembo ade”. To obtain accurate data, this qualitative research used in-depth interview to some indigenous people of Dompu and Bima who actively speak Bima language. The significant findings of this research is that the phrase kalembo ade and its lexical English translation enlarge heart have the same morphological rules which both are composed of prefix + adjective and noun. Syntactically, the phrase kalembo ade has the same syntactical rule with its lexical English translation enlarge heart. The two phrases are occupied by Verb Phrase (VP) which the transitive verbs enlarge and kalembo function as predicate (P), and the words ade and heart are occupied by Noun Phrase (NP) whose function as a Direct Object (DO). Another important finding in this study is that in everyday communication, Kalembo Ade has various meanings and functions based on the context uttered such as sorry in expression of apology, be patient in expression of sympathy or condolence, and be advised in asking one’s understandings. Similar studies which investigate morphological, syntactical, and semantic rules of other phrases are highly recommended for future studies.